2018
DOI: 10.1182/blood-2018-03-837153
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-associated thrombosis in patients with implanted ports: a prospective multicenter French cohort study (ONCOCIP)

Abstract: The need to accurately identify cancer outpatients at high risk of thrombotic complications is still unmet. In a prospective, multicenter cohort study (ONCOlogie et Chambres ImPlantables [ONCOCIP]), consecutive adult patients with a solid tumor and implanted port underwent 12-month follow-up. Our primary objective was to identify risk factors for (1) catheter-related thrombosis, defined as ipsilateral symptomatic upper-limb deep-vein thrombosis with or without pulmonary embolism, and (2) venous thromboembolism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 42 publications
2
61
2
3
Order By: Relevance
“…In both studies, the majority of patients were diagnosed with breast cancer or colorectal cancer [10,16]. A recently published prospective cohort study examining the rate of IVAD related VTE in 3032 patients across France found a rate of 3.8% [15]. This rate is higher than what was found in this study, and their population included patients who were on prophylactic and therapeutic anticoagulation, which may have decreased the rate of IVAD-related UEDVT.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In both studies, the majority of patients were diagnosed with breast cancer or colorectal cancer [10,16]. A recently published prospective cohort study examining the rate of IVAD related VTE in 3032 patients across France found a rate of 3.8% [15]. This rate is higher than what was found in this study, and their population included patients who were on prophylactic and therapeutic anticoagulation, which may have decreased the rate of IVAD-related UEDVT.…”
Section: Discussioncontrasting
confidence: 53%
“…The primary outcome of this study was symptomatic IVAD-related UEDVT defined as a symptomatic VTE in any deep vein throughout the course of the catheter, or symptomatic pulmonary embolism (PE) associated with the IVAD-related UEDVT [15]. These include the axillary, brachiocephalic, jugular and subclavian veins on the ipsilateral side of the IVAD insertion.…”
Section: Methodsmentioning
confidence: 99%
“…Third, both trials included symptomatic upper extremity DVT as part of the composite VTE outcome. Because of its low incidence and frequency co‐occurrence with other outcome events, it is challenging to pool the results as a separate endpoint; however, the ONCOCIP prospective cohort study showed that upper extremity DVT likely had different incidence and risk factors than PE and lower extremity DVT . Fourth, the utility weights in the EUT model were derived in older studies with predominately non‐cancer patients receiving either warfarin or LMWH .…”
Section: Discussionmentioning
confidence: 99%
“…B, Risk ratio for clinically relevant non-major bleeding (during on-treatment period) it is challenging to pool the results as a separate endpoint; however, the ONCOCIP prospective cohort study showed that upper extremity DVT likely had different incidence and risk factors than PE and lower extremity DVT. 32 Fourth, the utility weights in the EUT model were derived in older studies with predominately non-cancer patients receiving either warfarin or LMWH. 17 Although these utility weights were found to be similar in a more recent study, very few patients in either study included cancer patients receiving DOAC; this remains an important area of future research.…”
Section: Discussionmentioning
confidence: 99%
“…In einer anderen multizentrischen prospektiven Studie an 3032 Patienten differieren die Risikofaktoren für das Auftreten einer Katheter-assoziierten (an der oberen Extremität in der Umgebung des Ports) Thrombose von denen für das Auftreten einer nicht Katheter-assoziierten Thrombose [18]: Ein unabhängiger Risikofaktor für die portassoziierten VTs war die Implantation des Ports in die V. cephalica. Bei den nicht portassoziierten VTs ergaben sich u. a. das Vorliegen einer Anämie (Hb-Wert < 10 g/dl) sowie einer Leukozytose (> 11 × 10 9 /l) als unabhängige Risikofaktoren [18]. In unserer Studie zeigte sich im χ 2 -Test ein auffällig starker Zusammenhang zwischen dem Vorliegen eines Ports und dem Auftreten eines Gefäßverschlusses, wobei die genaue Lokalisation der VT (z.…”
Section: Portkatheter Als Risikofaktorunclassified